Gestión institucional y su relación con la calidad del servicio en una institución educativa pública de Callao - Elera Gómez, Rodomiro (2010)
This research aims to identify the relationship between institutional management and the quality of education services . It used a correlative descriptive design. In the sample included a total of 148 students in grade 5º high school and their parents, and all the teaching staff, to whom were administered a sample to collect their perceptions on these variables. Statistical treatment concluded that there is significant relationship between institutional management variable and the variable quality of education of 0.003 and 0.000 in teaching both students and parents in an alpha level of 0.05, in the school Mayer Dora district of Bellavista-Callao. There is also a significantrelationship between the dimensions (management leadership, strategic planning, evaluation of educational management , school climate, staff development and teacher performance) with the quality of educational services, test the hypothesis.